Gender-Based Pre-Service Teachers’ Academic Resilience - Mustofa, Ali; Harida, Ratri; Ro'is, Syamsuddin (STKIP PGRI Ponorogo Press, 2024)
Academic resilience is an important factor in determining student success. Any disparities that may exist between male and female students in the English education program are important in order to ensure that all students have equal opportunities for academic success. An academic resilience adaptation questionnaire was employed in this quantitative study with third semester English education program students. Despite being a smaller percentage of the third semester English education program population, this study indicated that more male students have a high level of academic resilience. Another finding was that male and female students share a similar percentage of students who had low levels of academic resilience. The results of this study support the findings that show gender has an effect on academic resilience.